MODEL PEMBELAJARAN SILAJARA BERBASIS CTL UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATERI MAKANAN DAN SISTEM PENCERNAAN MANUSIA - Kirana, Yulisia Rezky; Palennari, Muhiddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Conceptual understanding of food and the human digestive system remains a challenge in biology education because learning activities often rely on memorization and fail to meaningfully connect scientific concepts with real-life contexts. This literature study aims to examine and formulate the SILAJARA learning model (Observe, Identify, Perform, Analyze, Explain, Reflect, Apply) as an innovation based on Contextual Teaching and Learning (CTL), emphasizing contextual, reflective, and applicative learning experiences. The model was developed through an analysis of constructivist theory, CTL principles, and recent research findings related to contextual biology learning. The results of the review show that SILAJARA consists of seven structured learning stages that guide students from contextual observation to the application of values in daily life. The model is supported by essential components, including the social system, reaction principles, support system, and instructional as well as nurturant effects. Conceptually, SILAJARA has the potential to improve conceptual understanding, learning engagement, analytical skills, and reflective awareness of digestive health. Therefore, SILAJARA can serve as an adaptive and meaningful alternative learning model relevant to the needs of 21st-century biology education.